DRAFTING OF EMPLOYMENT CONTRACT AT FLORENCO COMPANY - Jiko Sastrawanto Ongko; Nur Hadiyati (Universitas Internasional Batam, 2022)
Demands between the rights and obligations of employees and company owners are common in a company, one of the reasons for this is that a valid and binding employment contract has not yet been formed in the company while the method for resolving this can be completed using the consultation method to obtain aspirations between the two parties and advocacy methods to initiate and complete a work contract that is valid and binding between the two parties, the result of the implementation is that after a negotiation process between the company owner and company employees regarding the rights and obligations of each party an agreement has been reached which is then made as a work contract that binds both parties, the suggestion for the next PkM is that after carrying out the manufacturing process it is better to carry out a monitoring process on the results of the PkM that have been completed.